Analisis penerapan akuntansi manajemen lingkungan pada PT. Gerbang Nusa Perkasa - Maralending, Joshua Antika; Pangemanan, Sifrid S.; Tirayoh, ⁠Victorina Z. (Manajemen Bisnis dan Keuangan Korporat, 2025)
Environmental damage is a problem that is often overlooked in the business world. This is due to the waste generated and overexploitation of the environment and not being managed properly. This is because companies and government agencies are not effective in implementing environmental management accounting. This study aims to determine how the analysis of the application of environmental management accounting at PT. Gerbang Nusa Perkasa. The analytical method used in this research is a qualitative descriptive method, and the results are clear: PT. Gerbang Nusa Perkasa has not yet implemented environmental management accounting. There are no detailed and specific environmental costs in the income statement, and the results of the income statement do not contain elements related to environmental management. This is indicated by the absence of an account in the accounting records that would disclose environmental management.